Sulfide electrolyte and preparation method thereof, solid-state battery and electronic equipment
Through liquid phase ball milling and sintering treatment, sulfide electrolytes with optimized particle size and particle size distribution are prepared, which solves the problem of sulfide electrolyte refinement in solid-state batteries and improves the electrochemical performance and rate performance of the battery.
Patent Information
- Application Number
- CN202411332010.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-07
AI Technical Summary
The sulfide electrolyte in solid-state batteries is difficult to refine into small-sized particles, resulting in a wide particle size distribution and a large specific surface area, which increases the side reaction with the positive electrode, making it difficult to improve battery performance.
Through liquid phase ball milling and sintering treatment, sulfide electrolytes with small particle size, narrow particle size distribution and small specific surface area are prepared. The specific steps include the first liquid phase ball milling, the first sintering treatment, the second sintering treatment and the second sintering treatment. For liquid phase ball milling, the control particle size is between 10nm and 5000nm, the specific surface area is between 1m2/g and 15m2/g, and the particle size distribution is between 0.9≤(D90-D10)/D50≤2.
Effective contact between the sulfide electrolyte and the positive or negative electrode active material is achieved, ion conductivity is improved, side reactions are reduced, and electrochemical performance and rate cycling performance of solid-state batteries are improved.
Smart Images

Figure CN119275332A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a sulfide electrolyte and a preparation method thereof, a solid-state battery and an electronic device. Background Art
[0002] With the rapid development of electric vehicles, people are paying more and more attention to the safety performance of batteries. Lithium-ion batteries often use liquid organic electrolytes, which are prone to battery leakage, resulting in safety hazards such as easy combustion, corrosion, and explosion. All-solid-state batteries use solid electrolytes instead of flammable liquid electrolytes, so they are regarded as the next generation of energy storage devices with high safety and energy density.
[0003] The positive and negative electrodes of solid-state batteries usually contain various solid materials, such as active materials, electrolyte materials, conductive carbon and binders. Various solid-solid interfaces are formed between these components, so it is difficult to achieve uniform distribution of these solid materials and ensure close contact between these interfaces. Moreover, compared with liquid electrolytes, solid electrolytes have natural defects such as poor chemical stability, hard texture, non-flow characteristics, gaps at the interface and side reactions. In response to the above problems, if small-sized electrolyte particles, especially nano-scale particles, are used, it is possible to form a better contact interface with the active materials, conductive carbon and binder, which is conducive to improving ion conduction and enhancing battery performance.
[0004] Among solid electrolytes, sulfide electrolytes have high ionic conductivity, low cost, and a relatively small Young's modulus, so they have excellent processability and can form a good solid / solid interface in solid-state batteries, and are widely used. However, correspondingly, due to its soft material, it is difficult to refine it to obtain a small-sized sulfide solid electrolyte. Moreover, even if a small-sized sulfide solid electrolyte is prepared, the electrolyte will have problems such as a wide particle size distribution and a large specific surface area, which will increase the side reaction between it and the positive electrode, making it difficult to effectively improve the battery performance. Summary of the invention
[0005] Based on this, the present application provides a sulfide electrolyte with a smaller particle size, a narrower particle size distribution and a smaller specific surface area, and a preparation method thereof, a solid-state battery and an electronic device, which can effectively improve the electrochemical performance of the solid-state battery.
[0006] The first aspect of the present application provides a sulfide electrolyte, wherein the median particle size D50 and the specific surface area of the sulfide electrolyte are 10nm to 5000nm and 1m 2 / g~15m 2 / g, and the particle size distribution of the sulfide electrolyte satisfies: 0.9≤(D90-D10) / D50≤2.
[0007] In some embodiments, the sulfide electrolyte satisfies at least one of the following conditions:
[0008] (1) The sulfide electrolyte satisfies the chemical formula Li 7-x P 1-y M y S 6-x-z N z W x , wherein 0≤x≤2, 0≤y<1, 0≤z<1, M includes at least one of As, Ge, Si, Sn, Sb, Nb, Al, N includes at least one of O and Se, and W includes at least one of halogen atoms;
[0009] (2) The ionic conductivity of the sulfide electrolyte is 1 mS / cm to 15 mS / cm.
[0010] In some embodiments, the sulfide electrolyte satisfies at least one of the following conditions:
[0011] (1) The D50 of the sulfide electrolyte is 20 nm to 500 nm, and can be optionally 250 nm to 300 nm;
[0012] (2) The specific surface area of the sulfide electrolyte is 6 m 2 / g~13m 2 / g, optional 6m 2 / g~8m 2 / g;
[0013] (3) The D90 of the sulfide electrolyte is 400nm to 450nm;
[0014] (4) The D10 of the sulfide electrolyte is 100 nm to 150 nm;
[0015] (5) The sphericity of the particles of the sulfide electrolyte is 0.5 to 1.
[0016] A second aspect of the present application provides a method for preparing a sulfide electrolyte, comprising:
[0017] The sulfide electrolyte raw material is subjected to a first liquid-phase ball milling to prepare a precursor slurry, wherein the sulfide electrolyte raw material is a mixture comprising a lithium source, a phosphorus source, a sulfur source and a halogen source;
[0018] The precursor slurry is subjected to a first sintering treatment and a second sintering treatment in sequence to prepare a sulfide electrolyte intermediate product, wherein the temperature of the first sintering treatment is less than the temperature of the second sintering treatment;
[0019] The sulfide electrolyte intermediate product is subjected to a second liquid-phase ball milling and then the ball milling solvent is removed to prepare a sulfide electrolyte, wherein the median particle size D50 and the specific surface area of the sulfide electrolyte are 10 nm to 5000 nm and 1 m 2 / g~13m 2 / g, and the particle size distribution of the sulfide electrolyte satisfies: 0.9≤(D90-D10) / D50≤1.
[0020] In some embodiments, at least one of the following conditions is met:
[0021] (1) The temperature of the first sintering treatment is 120° C. to 300° C.;
[0022] (2) The temperature of the second sintering treatment is 350°C to 700°C.
[0023] In some embodiments, at least one of the following conditions is met:
[0024] (1) The average particle size of the sulfide electrolyte raw material is 0.5 μm to 10 μm, and can be optionally 0.5 μm to 8 μm;
[0025] (2) In the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source and the halogen source is ≤2 μm;
[0026] (3) The lithium source includes at least one of lithium sulfide, lithium oxide and lithium carbonate, and lithium sulfide may be selected;
[0027] (4) The phosphorus source includes at least one of phosphorus pentasulfide and phosphorus trisulfide;
[0028] (5) The sulfur source includes at least one of lithium sulfide, phosphorus pentasulfide and phosphorus trisulfide;
[0029] (6) The halogen source comprises at least one of lithium chloride and lithium bromide;
[0030] (7) The sulfide electrolyte raw material further comprises at least one of a simple substance of an M element, a compound containing an M element, and a compound containing an N element, wherein the M element comprises at least one of As, Ge, Si, Sn, Sb, Nb, and Al, and the N element comprises at least one of O and Se;
[0031] Optionally, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source, the halogen source and the compound containing the element M is ≤2 μm;
[0032] Optionally, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source, the halogen source and the N-containing element compound is ≤2 μm;
[0033] Optionally, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source, the halogen source, the M-containing compound and the N-containing compound is ≤2 μm.
[0034] In some embodiments, at least one of the following conditions is met:
[0035] (1) After the first liquid phase ball milling, the particle size of the prepared precursor slurry is 1 μm to 7 μm;
[0036] (2) the ball milling solvents used in the first liquid-phase ball milling and the second liquid-phase ball milling each independently include at least one of an ether organic solvent, an ester organic solvent and a nitrile organic solvent;
[0037] Optionally, the first liquid-phase ball milling and the second liquid-phase ball milling use the same ball milling solvent;
[0038] Optionally, the ether organic solvent includes at least one of dimethyl ether, dipropyl ether, dibutyl ether, methyl ethyl ether and anisole;
[0039] Optionally, the ester organic solvent includes at least one of ethyl acetate, butyl butyrate, hexyl butyrate and isobutyl isobutyrate;
[0040] Optionally, the nitrile organic solvent includes at least one of acetonitrile, isobutyronitrile, tert-butyronitrile and benzonitrile.
[0041] In some embodiments, at least one of the following conditions is met:
[0042] (1) The ball-to-material ratio of the first liquid-phase ball milling is 5:1 to 40:1, and the liquid-to-material ratio is 1:1 to 10:1;
[0043] (2) The ball-to-material ratio of the second liquid phase ball milling is 4:1 to 20:1, and the liquid-to-material ratio is 1:1 to 5:1.
[0044] The third aspect of the present application provides a solid-state battery, comprising the sulfide electrolyte of the first aspect of the present application or the sulfide electrolyte prepared by the preparation method of the second aspect of the present application.
[0045] The fourth aspect of the present application provides an electronic device, comprising the solid-state battery of the third aspect of the present application.
[0046] The electronic device of the present application includes the solid-state battery provided by the present application, and thus has at least the same advantages as the solid-state battery.
[0047] When the median particle size, specific surface area and particle size distribution of the sulfide electrolyte are respectively in the above ranges, the three can form a mutual coordination, which can not only increase the effective contact area between the sulfide electrolyte and the active material in the positive electrode or negative electrode, improve the utilization rate of the active material, form a continuous ion conductive network, and improve ion conductivity. It can also effectively reduce the uneven contact coating between particles, which can effectively reduce the occurrence of side reactions between the sulfide electrolyte and the positive electrode or negative electrode, reduce the tortuosity of the electrode ion migration, and improve the electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is the surface morphology of the sulfide electrolyte prepared in Example 1. DETAILED DESCRIPTION
[0049] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0050] For simplicity, this application only explicitly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unclearly recorded range; and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, although not clearly recorded, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art in the technical field of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. It should be noted that, unless otherwise specified, the term "and / or" used herein includes any and all combinations of one or more related listed items, and "above" and "below" include the number, and the meaning of "multiple" in "one or more" is more than two.
[0052] Herein, when it comes to a numerical interval (i.e., a numerical range), unless otherwise specified, the distribution of the optional numerical values in the numerical interval is considered to be continuous, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical interval, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers in the numerical interval, including the two endpoint integers of the numerical range, and each integer between the two endpoints, is equivalent to directly listing each integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be combined. In other words, unless otherwise specified, the numerical ranges disclosed herein should be understood to include any and all sub-ranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, a percentage, a ratio, etc. "Numerical interval" allows broadly including numerical interval types such as percentage intervals, ratio intervals, and ratio intervals.
[0053] In this article, if there are multiple steps involved in the method flow, unless there is a clear different description in this article, there is no strict order restriction for the execution of these steps, and they can be executed in other orders than described. Moreover, any step can include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and their execution order is not necessarily sequential, but can be executed in turn, alternating or simultaneously with other steps or parts of sub-steps or stages of other steps.
[0054] The above application content of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0055] During the research process, the inventors found that in solid-state batteries, sulfide electrolytes are prone to side reactions with positive electrode active materials, conductive carbon, etc. in the composite positive electrode; especially for small-particle sulfide electrolytes, although they can enhance the contact between solid particles and form a better solid / solid interface; however, small-particle sulfide electrolytes usually have a larger specific surface area, which can easily lead to the intensification of side reactions between them and the positive electrode (that is, the polysulfides produced between the sulfide electrolyte and the positive electrode will precipitate and dissolve on the positive electrode), resulting in increased internal resistance and decreased electrochemical performance of the battery.
[0056] To solve the above problems, the present application proposes the following technical solution, which can reduce the particle specific surface area (BET) and particle size distribution (span value) while obtaining a small-sized sulfide electrolyte, thereby reducing the side reactions of the obtained sulfide electrolyte with the active materials, conductive carbon and other materials in the positive electrode, and improving the ionic conductivity, and finally obtaining a sulfide electrolyte suitable for the positive and negative electrodes of a solid-state battery.
[0057] In a first aspect, the present application provides a sulfide electrolyte, wherein the median particle size D50 and the specific surface area of the sulfide electrolyte are 10 nm to 5000 nm and 1 m 2 / g~15m 2 / g, and the particle size distribution of the sulfide electrolyte satisfies: 0.9≤(D90-D10) / D50≤2.
[0058] When the median particle size, specific surface area and particle size distribution of the sulfide electrolyte are respectively in the above range, the three can form a mutual coordination, which can not only increase the effective contact area between the sulfide electrolyte and the active material in the positive or negative electrode, improve the utilization rate of the active material, form a continuous ion conductive network, and improve ion conductivity. It can also effectively reduce the uneven contact coating between particles, which can effectively reduce the occurrence of side reactions between the sulfide electrolyte and the positive or negative electrode, reduce the tortuosity of the electrode ion migration, and improve the electrochemical performance. At the same time, it is also conducive to the improvement of the tap density of the sulfide electrolyte, which is conducive to improving the rate cycle performance of the positive and negative sides of the battery.
[0059] In some embodiments, the median particle size D50 of the sulfide electrolyte may be 10 nm, 50 nm, 100 nm, 500 nm, 1000 nm, 2000 nm, 3000 nm, 4000 nm, 5000 nm, or a range thereof.
[0060] In some embodiments, the specific surface area of the sulfide electrolyte may be 1 m 2 / g,2m 2 / g,3m 2 / g,4m 2 / g,5m 2 / g,6m 2 / g,7m 2 / g,8m 2 / g,9m 2 / g,10m 2 / g,11m 2 / g,12m 2 / g,13m 2 / g,14m 2 / g,15m 2 / g or within a range consisting of any of the above values.
[0061] In some embodiments, the ionic conductivity of the sulfide electrolyte is 1 mS / cm to 15 mS / cm. For example, the ionic conductivity may be 1 mS / cm, 2 mS / cm, 3 mS / cm, 4 mS / cm, 5 mS / cm, 6 mS / cm, 7 mS / cm, 8 mS / cm, 9 mS / cm, 10 mS / cm, 11 mS / cm, 12 mS / cm, 13 mS / cm, 14 mS / cm, 15 mS / cm or within a range of any of the above values. In this way, the ionic conductivity is improved, and the solid-state battery can have excellent rate performance.
[0062] In some embodiments, the D50 of the sulfide electrolyte is 20 nm to 500 nm. For example, D50 may be 20 nm, 40 nm, 60 nm, 80 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm or any range thereof.
[0063] In some embodiments, the D50 of the sulfide electrolyte is 250 nm to 300 nm, for example, D50 can be 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm or in a range of any of the above values. In this way, the coordination between the median particle size, the specific surface area and the particle size distribution can be further enhanced, and the sulfide electrolyte can have better contact with the active material, better solid-solid contact, and higher utilization of the active material.
[0064] In some embodiments, the specific surface area of the sulfide electrolyte is 6 m 2 / g~13m 2 / g. For example, the specific surface area can be 6m 2 / g,6.5m 2 / g,7m 2 / g,7.5m 2 / g,8m 2 / g,8.5m 2 / g,9m 2 / g,9.5m 2 / g,10m 2 / g, 10.5m 2 / g,11m 2 / g, 11.5m 2 / g,12m 2 / g, 12.5m 2 / g,13m 2 / g or within the range of any of the above values. Optionally, the specific surface area of the sulfide electrolyte is 6m 2 / g~8m 2 In this way, the coordination between the median particle size, specific surface area and particle size distribution can be further enhanced, and the side reactions between the sulfide electrolyte and active materials, conductive carbon and other substances can be further reduced, thereby reducing the interface impedance and improving the electrochemical performance.
[0065] In some embodiments, (D90-D10) / D50 can be 0.9, 0.91, 0.92, 0.93, 0.94, 0.95, 0.96, 0.97, 0.98, 0.99, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2 or within the range of any of the above values. Optionally, the particle size distribution of the sulfide electrolyte satisfies: 0.9≤(D90-D10) / D50≤1. In this way, the coordination between the median particle size, the specific surface area and the particle size distribution can be further enhanced, and the particle size distribution of the sulfide electrolyte can be made more uniform, thereby providing a more stable ion conductive network.
[0066] In some embodiments, the sphericity of the particles of the sulfide electrolyte is 0.5 to 1. For example, the sphericity may be 0.5, 0.6, 0.7, 0.8, 0.9, 1, or any range thereof. In this way, the morphology of the particles of the sulfide electrolyte is relatively regular, which is conducive to obtaining a narrower particle size distribution.
[0067] In some embodiments, the D90 of the sulfide electrolyte is 400 nm to 450 nm. For example, D90 may be 400 nm, 410 nm, 420 nm, 430 nm, 440 nm, 450 nm, or any range thereof. In this way, the sulfide electrolyte can have better contact with the active material, better solid-solid contact, and higher utilization of the active material.
[0068] In some embodiments, the D10 of the sulfide electrolyte is 100 nm to 150 nm. For example, D10 may be 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, or any range thereof. In this way, the sulfide electrolyte can have better contact with the active material, better solid-solid contact, and higher utilization of the active material.
[0069] In some embodiments, the sulfide electrolyte satisfies the chemical formula Li 7-x P 1-y M y S 6-x-z N z Wx , wherein 0≤x≤2, 0≤y<1, 0≤z<1, M includes at least one of As, Ge, Si, Sn, Sb, Nb, and Al, N includes at least one of O and Se, and Z includes at least one of halogen atoms.
[0070] In a second aspect, the present application provides a method for preparing a sulfide electrolyte, which can be used to prepare the sulfide electrolyte of the first aspect of the present application, and may include the following steps S1 to S3.
[0071] S1: performing a first liquid-phase ball milling on a sulfide electrolyte raw material to prepare a precursor slurry, wherein the sulfide electrolyte raw material is a mixture comprising a lithium source, a phosphorus source, a sulfur source and a halogen source;
[0072] S2: subjecting the precursor slurry to a first sintering treatment and a second sintering treatment in sequence to prepare a sulfide electrolyte intermediate product, wherein the temperature of the first sintering treatment is less than the temperature of the second sintering treatment;
[0073] S3: subjecting the sulfide electrolyte intermediate product to a second liquid-phase ball milling and removing the ball milling solvent to prepare a sulfide electrolyte, wherein the median particle size D50 and specific surface area of the sulfide electrolyte are 10 nm to 5000 nm and 1 m 2 / g~15m 2 / g, and the particle size distribution of the sulfide electrolyte satisfies: 0.9≤(D90-D10) / D50≤2.
[0074] The traditional preparation method of sulfide electrolytes usually includes multiple and multi-mode crushing treatments of intermediate products or final products during the preparation process. This can easily cause the sulfide electrolyte particles to have irregular morphology (such as flaky particles) and poor particle sphericity. It can also easily cause the sulfide electrolyte particle size distribution to be wide and the particles to have more surface defects. These factors can easily lead to an excessively large specific surface area when the particle size is constant.
[0075] In view of this, the preparation method provided in the present application, through the mutual cooperation of steps S1 to S3, can obtain a sulfide electrolyte with regular particle morphology and reduce its surface defects, so that it has a small particle size while maintaining a low specific surface area and a narrow particle size distribution.
[0076] In some embodiments, the temperature of the first sintering treatment is 120°C to 300°C. For example, the temperature of the first sintering treatment can be 120°C, 150°C, 200°C, 250°C, 300°C or in the range of any of the above values. The temperature of the first sintering treatment is controlled within the above range, and while removing the ball milling solvent, it can prevent the ball milling solvent from boiling violently when it is removed, which is beneficial to the uniform heating of the precursor slurry and complete reaction, thereby facilitating the improvement of ionic conductivity and obtaining a sulfide electrolyte with a concentrated particle size distribution and uniform particle shape.
[0077] In some embodiments, the temperature of the second sintering treatment is 350°C to 700°C. For example, the temperature of the second sintering treatment can be 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C or any range thereof. The temperature of the second sintering treatment is controlled within the above range, which is conducive to forming a sulfide electrolyte with concentrated particle size distribution, uniform particle shape and high ionic conductivity.
[0078] In some embodiments, the average particle size of the sulfide electrolyte raw material is 0.5 μm to 10 μm, and can be 0.5 μm to 8 μm, which is conducive to the full and uniform mixing of the raw materials during the liquid phase ball milling process, thereby facilitating the formation of a sulfide electrolyte with a concentrated particle size distribution and uniform particle shape.
[0079] In some embodiments, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source and the halogen source is ≤ 2 μm. This facilitates full and uniform mixing of the raw materials during liquid phase ball milling, thereby facilitating the formation of a sulfide electrolyte with concentrated particle size distribution, uniform particle shape and high ionic conductivity.
[0080] In some embodiments, the lithium source includes at least one of lithium sulfide, lithium oxide and lithium carbonate, and may be lithium sulfide.
[0081] In some embodiments, the phosphorus source includes at least one of phosphorus pentasulfide and phosphorus trisulfide.
[0082] In some embodiments, the sulfur source includes at least one of lithium sulfide, phosphorus pentasulfide, and phosphorus trisulfide.
[0083] In some embodiments, the halogen source includes at least one of lithium chloride and lithium bromide.
[0084] In some embodiments, the sulfide electrolyte raw material further comprises at least one of a simple M element, a compound containing the M element, and a compound containing the N element, the M element comprises at least one of As, Ge, Si, Sn, Sb, Nb, and Al, and the N element comprises at least one of O and Se.
[0085] In some embodiments, the compound containing the M element includes at least one of As2S5, As2S3, GeO2, SiO2, SnO2, Sb2S5, Sb2O3, Sb2O5, NbO, Nb2O5, Al2O3, GeCl4, SiCl4, SnCl4, SbCl3, AlCl3, GeS2, SiS2, Sb2S3, and GeSe.
[0086] In some embodiments, the N-element compound includes at least one of Li2O, GeO2, SiO2, SnO2, Sb2O3, Sb2O5, NbO, Nb2O5, Al2O3, SeO2, SeO3, SeCl4, SeS, and GeSe.
[0087] In some embodiments, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source, the halogen source and the compound containing the element M is ≤2 μm.
[0088] In some embodiments, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size of any two of the lithium source, the phosphorus source, the sulfur source, the halogen source and the N-containing element compound is ≤2 μm.
[0089] In some embodiments, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size of any two of the lithium source, the phosphorus source, the sulfur source, the halogen source, the M-containing compound and the N-containing compound is ≤2 μm.
[0090] In some embodiments, the sulfide electrolyte raw material can be prepared by the following method: take a certain amount of lithium source, phosphorus source, sulfur source, halogen source, optional M-containing compound, and optional N-containing compound, mix and crush in a high-speed mixer for 3 minutes to 10 minutes, and obtain a sulfide electrolyte with an average particle size of 0.5 μm to 10 μm. In this way, the particle size and uniformity of the raw materials can be reduced so that they can be fully and evenly mixed during the liquid phase ball milling process.
[0091] In some embodiments, after the first liquid-phase ball milling, the particle size of the prepared precursor slurry is 1 μm to 7 μm. For example, the particle size can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or within the range of any of the above values. Compared with the product obtained by sintering after dry ball milling, the product obtained by sintering after the first liquid-phase ball milling has a smaller particle size, more uniformity and higher sphericity, and fewer surface defects; and the ball milling process does not need to open the can to loosen the material, and the process can be scaled up.
[0092] In some embodiments, the ball milling solvents used in the first liquid-phase ball milling and the second liquid-phase ball milling each independently include at least one of an ether organic solvent, an ester organic solvent, and a nitrile organic solvent.
[0093] The ball milling solvent can act as a surfactant, which can inhibit the agglomeration of microparticles during the liquid phase ball milling process, which is beneficial to reducing the particle size and improving the particle uniformity. At the same time, when the above-mentioned ball milling solvent is used, the sulfide electrolyte raw material can present a stable suspension state in the solvent instead of quickly settling in the solvent, and the solvent has low reactivity with the sulfide electrolyte raw material, which can disperse the electrolyte raw material and promote the reduction of particle size during the pulverization process.
[0094] In some embodiments, the first liquid-phase ball milling and the second liquid-phase ball milling use the same ball milling solvent. This can prevent the introduction of other solvents, which may cause solvent residues; on the other hand, different solvents may have different degrees of side reactions during the ball milling process, and using the same ball milling solvent can avoid the occurrence of such side reactions.
[0095] In some embodiments, the ether organic solvent includes at least one of dimethyl ether, dipropyl ether, dibutyl ether, methyl ethyl ether and anisole.
[0096] In some embodiments, the ester organic solvent includes at least one of ethyl acetate, butyl butyrate, hexyl butyrate, and isobutyl isobutyrate.
[0097] In some embodiments, the nitrile organic solvent includes at least one of isobutyronitrile, tert-butyronitrile and benzonitrile.
[0098] In some embodiments, the ball-to-material ratio of the first liquid-phase ball milling is 5:1-40:1, and the liquid-to-material ratio is 1:1-10:1. For example, the ball-to-material ratio can be 5:1, 8:1, 10:1, 13:1, 16:1, 19:1, 20:1, 22:1, 25:1, 28:1, 31:1, 34:1, 37:1, 40:1, or within the range of any of the above values. The liquid-to-material ratio can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or within the range of any of the above values.
[0099] It can be understood that the "ball-to-material ratio of the first liquid-phase ball milling" mentioned in this application refers to the mass ratio of the ball milling medium (such as ball milling beads) to the sulfide electrolyte raw material during the first liquid-phase ball milling; and the "liquid-to-material ratio" refers to the mass ratio of the ball milling solvent to the sulfide electrolyte raw material.
[0100] In some embodiments, the ball-to-material ratio of the second liquid-phase ball milling is 4:1 to 20:1, and the liquid-to-material ratio is 1:1 to 5:1. For example, the ball-to-material ratio can be 4:1, 6:1, 8:1, 10:1, 12:1, 14:1, 16:1, 18:1, 20:1 or within the range of any of the above values. The liquid-to-material ratio can be 1:1, 2:1, 3:1, 4:1, 5:1 or within the range of any of the above values. The second liquid-phase ball milling can further reduce the particle size of the sulfide electrolyte, narrow the particle size range, and uniformly form a uniform particle morphology.
[0101] It can be understood that the "ball-to-material ratio of the second liquid-phase ball milling" mentioned in the present application refers to the mass ratio of the ball milling medium (such as ball milling beads) to the sulfide electrolyte intermediate product during the second liquid-phase ball milling; and the "liquid-to-material ratio" refers to the mass ratio of the ball milling solvent to the sulfide electrolyte intermediate product.
[0102] In some embodiments, after removing the milling solvent after the second liquid-phase ball milling of the sulfide electrolyte intermediate product, step S3 may further include: crushing and classifying the product after the milling solvent is removed.
[0103] In a third aspect, the present application provides a solid-state battery, which includes the sulfide electrolyte of the first aspect of the present application or the sulfide electrolyte prepared by the preparation method of the second aspect of the present application.
[0104] It can be understood that in a solid-state battery, the sulfide electrolyte can be compounded in the positive electrode, in the negative electrode, or in both the positive electrode and the negative electrode at the same time, and the specific selection can be made according to actual needs.
[0105] In a fourth aspect, the present application provides an electronic device comprising the solid-state battery of the third aspect of the present application.
[0106] In some embodiments, the type of electronic device is not particularly limited, and it can be any electronic device known in the prior art. For example, the electronic device can include, but is not limited to, power tools, electric cars, laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, etc.
[0107] Example
[0108] The following are specific examples, which more specifically describe the contents disclosed in this application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0109] Example 1
[0110] (1) In a glove box with an inert gas atmosphere, 34.4685 g of Li2S, 41.6829 g of P2S5, and 23.8485 g of LiCl (molar mass ratio of 4:1:3) were weighed and placed in a high-speed mixer, and mixed and crushed at high speed for 5 minutes to obtain a sulfide electrolyte raw material with an average particle size of about 5 μm, and in the sulfide electrolyte raw material, the absolute value of the difference in the average particle size of any two of Li2S, P2S5, and LiCl was ≤2 μm.
[0111] (2) The sulfide electrolyte raw material was transferred to a vacuum ball mill, and 5 mm zirconia ball milling beads were added to make the ball-to-material ratio 20:1; isobutyl isobutyrate was then added to make the liquid-to-material ratio 4:1. After sealing, the mixture was ball milled at 450 rpm for 10 h to obtain a precursor slurry.
[0112] (3) The precursor slurry was transferred to a clean corundum crucible, and then sintered in a box furnace at a low temperature of 155°C with a heating rate of 2°C / min for 8 hours; then sintered at a high temperature of 500°C for 12 hours.
[0113] (4) The product obtained in step (3) was mixed with 2 mm zirconium oxide ball milling beads with a ball-to-material ratio of 8:1 and isobutyl isobutyrate with a liquid-to-material ratio of 3:1, and the mixture was sealed and ball milled for 8 h.
[0114] (5) The ball-milled product is placed in a vacuum oven for drying to remove the solvent, and then the product is graded using a jet mill to obtain a sulfide electrolyte Li 5.5 PS 4.5 Cl1.5 .
[0115] Example 2
[0116] The preparation method is similar to that of Example 1, with the main differences being that in step (2), isobutyl isobutyrate is replaced by an equal mass of anisole; in step (3), the low-temperature sintering temperature is 160° C.; and in step (4), isobutyl isobutyrate is replaced by an equal mass of anisole.
[0117] Example 3
[0118] The preparation method is similar to that of Example 1, with the main differences being that in step (2), isobutyl isobutyronitrile is used instead of isobutyl isobutyrate in an equal amount; in step (3), the low-temperature sintering temperature is 120° C.; and in step (4), isobutyl isobutyronitrile is used instead of isobutyl isobutyrate in an equal amount.
[0119] Example 4
[0120] The preparation method is similar to that of Example 1, with the main differences being that in step (2), isobutyl isobutyrate is replaced by an equal mass of hexyl butyrate; in step (3), the low-temperature sintering temperature is 210° C.; and in step (4), isobutyl isobutyrate is replaced by an equal mass of hexyl butyrate.
[0121] Example 5
[0122] The preparation method is similar to that of Example 1, with the main difference being that in step (3), the low-temperature sintering temperature is 110°C.
[0123] Example 6
[0124] The preparation method is similar to that of Example 1, with the main difference being that in step (3), the low-temperature sintering temperature is 320°C.
[0125] Example 7
[0126] The preparation method is similar to that of Example 1, except that in step (4), an equal amount of anisole is used to replace isobutyl isobutyrate.
[0127] Example 8
[0128] The preparation method is similar to that of Example 1, with the main difference being that in step (1), the crushing time is about 3 minutes, so that the average particle size of the sulfide electrolyte raw material is about 10 μm.
[0129] Example 9
[0130] The preparation method is similar to that of Example 1, with the main difference being that in step (1), the crushing time is about 4 minutes, so that the average particle size of the sulfide electrolyte raw material is about 8 μm.
[0131] Example 10
[0132] The preparation method is similar to that of Example 1, except that: in step (1), 26.8139 g of Li2S, 30.8969 g of P2S5, 38.8766 g of LiBr, 3.0412 g of Ge2S5, and 0.3713 g of Li2O are weighed in a glove box under an inert gas atmosphere and placed in a high-speed mixer, and the absolute value of the difference in the average particle size of any two of the sulfide electrolyte raw materials is ≤ 2 μm; in step (5), a sulfide electrolyte Li 5.5 P 0.933 Ge 0.067 S 4.4585 O 0.0415 Br 1.5 .
[0133] Embodiment 11
[0134] The preparation method is similar to that of Example 1, except that: in step (1), 26.5814 g of Li2S, 30.5889 g of P2S5, 38.4852 g of LiBr, 3.9767 g of Sb2S5, and 0.3676 g of Li2O are weighed in a glove box under an inert gas atmosphere and placed in a high-speed mixer, and the absolute value of the difference in the average particle size of any two of the sulfide electrolyte raw materials is ≤ 2 μm; in step (5), a sulfide electrolyte Li 5.5 P 0.933 Sb 0.067 S 4.4585 O 0.0415 Br 1.5 .
[0135] Example 12
[0136] The preparation method is similar to that of Example 1, with the main difference being that in step (2), the ball-to-material ratio is 5:1.
[0137] Example 13
[0138] The preparation method is similar to that of Example 1, with the main difference being that in step (2), the ball-to-material ratio is 40:1.
[0139] Embodiment 14
[0140] The preparation method is similar to that of Example 1, with the main difference being that in step (2), the liquid-to-solid ratio is 1:1.
[0141] Embodiment 15
[0142] The preparation method is similar to that of Example 1, with the main difference being that in step (2), the liquid-to-solid ratio is 10:1.
[0143] Example 16
[0144] The preparation method is similar to that of Example 1, with the main difference being that in step (4), the ball-to-material ratio is 4:1.
[0145] Embodiment 17
[0146] The preparation method is similar to that of Example 1, with the main difference being that in step (4), the ball-to-material ratio is 20:1.
[0147] Embodiment 18
[0148] The preparation method is similar to that of Example 1, with the main difference being that in step (4), the ball-to-material ratio is 1:1.
[0149] Embodiment 19
[0150] The preparation method is similar to that of Example 1, with the main difference being that in step (4), the ball-to-material ratio is 5:1.
[0151] Comparative Example 1
[0152] The preparation method is similar to that of Example 1, with the main difference being that the second liquid phase ball milling in step (4) is omitted.
[0153] Comparative Example 2
[0154] The preparation method is similar to that of Example 1, with the main difference being that in steps (2) and (4), isobutyl isobutyrate is not added (i.e., dry ball milling).
[0155] The sulfide electrolytes prepared in Examples 1 to 19 and Comparative Examples 1 to 2 were subjected to relevant performance tests, and the test results are shown in Tables 1 and 2 below.
[0156] Among them, the test conditions or test standards for each performance test item are as follows:
[0157] (1) Average particle size of electrolyte raw materials, average particle size of precursor slurry, D50, D90, and D10 of sulfide electrolyte
[0158] Take samples of the tested product and use a laser particle size analyzer (HELOS / GRADIS) to test the particle size distribution.
[0159] (2) Specific surface area (BET)
[0160] The electrolyte product was sampled and the particle size distribution was tested using a laser particle size analyzer (ipore 450), thereby determining the BET value.
[0161] (3) Ionic conductivity
[0162] Weigh 0.2g of electrolyte material and load it into the battery compartment. Cold-press the tablet at 300Mpa, measure the thickness of the electrolyte layer, place blocking electrodes on both sides of the electrolyte layer, and complete the assembly of the impedance test mold. The assembled impedance mold is left at 27°C for 2h, and the ionic conductivity of the sulfide electrolyte is tested by the AC impedance method.
[0163] (4) Electrochemical energy test
[0164] Composite positive electrode sheet preparation:
[0165] NCM, the sulfide electrolyte obtained in the embodiment, VGCF, and NBR were mixed and dissolved in xylene at a ratio of 85:15:1:1 to prepare a positive electrode slurry, and then the positive electrode slurry was coated on an aluminum foil, and the electrode piece was placed in a vacuum oven at 60° C. and vacuum dried for 12 hours to obtain a composite positive electrode.
[0166] Battery preparation:
[0167] Weigh 0.15 g of the sulfide electrolyte obtained in the example, pressurize it at 300 MPa for 1 minute in a mold battery, use In as the negative electrode, and place the coated composite positive electrode sheet as the positive electrode in a mold battery and pressurize it at 400 MPa for 1 minute to prepare a solid-state battery.
[0168] Solid-state battery electrochemical performance testing
[0169] The solid-state battery was charged and discharged at constant current at 0.1C, 0.2C, and 0.5C at 25°C with a cut-off voltage of 1.2 to 3.65V, and then cyclically charged and discharged at a rate of 0.5C. The rate of 0.5C / 0.1C is the battery discharge capacity at a rate of 0.5C divided by the battery discharge capacity at a rate of 0.1C, and the 200-week cycle retention rate is the discharge capacity at a rate of 0.5C in the 200th week divided by the discharge capacity at the first week.
[0170] Table 1
[0171]
[0172] Table 2
[0173]
[0174] In the above table, by comparing the examples with the comparative examples, it can be seen that the sulfide electrolyte prepared by the preparation method of the present application has a smaller particle size, a narrower particle size distribution and a smaller specific surface area; subsequently, the solid-state battery composed of the sulfide electrolyte has higher electrochemical performance.
[0175] By comparing each embodiment with Comparative Example 1, it can be seen that the second liquid phase ball milling is beneficial to reducing the particle size (D50, D90, D10) of the sulfide electrolyte, narrowing the particle size range (or reducing the particle size distribution), thereby facilitating the formation of a uniform particle morphology (see Figure 1 ), and is conducive to the improvement of the corresponding solid-state battery rate and cycle retention rate. Comparing each embodiment with Comparative Example 2, it can be seen that compared with the dry ball milling method, the wet ball milling can effectively reduce the particle size, particle size distribution and specific surface area of the sulfide electrolyte, and is conducive to the improvement of the charge and discharge capacity, rate and cycle retention rate of the solid-state battery.
[0176] By comparing Examples 1 and 8 to 9, it can be seen that the average particle size of the sulfide electrolyte raw material will affect the particle size, particle size distribution, specific surface area, and sphericity of the sulfide electrolyte finally formed, and will affect the electrochemical properties of the corresponding solid-state battery; and when the average particle size of the sulfide electrolyte raw material is 5 μm to 8 μm, the particle size, particle size distribution, specific surface area, and sphericity of the sulfide electrolyte are smaller, and the first-week discharge capacity, first-week efficiency, and cycle retention rate of the battery are higher.
[0177] Comparing Examples 1, 12-13, and Examples 1, 14-15, it can be seen that the ball-to-material ratio and liquid-to-material ratio of the first ball milling will affect the particle size, particle size distribution, specific surface area, sphericity, etc. of the sulfide electrolyte, and then affect the capacity, rate and cycle performance of the corresponding solid-state battery. Comparing Examples 1, 16-17, and Examples 1, 18-19, it can be seen that the ball-to-material ratio and liquid-to-material ratio of the second ball milling will affect the particle size, particle size distribution, specific surface area, sphericity, etc. of the sulfide electrolyte, and then affect the capacity, rate and cycle performance of the corresponding solid-state battery.
[0178] In addition, from Figure 1 It can be seen that the sulfide electrolyte prepared in Example 1 has a relatively uniform particle morphology.
[0179] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0180] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A sulfide electrolyte, characterized in that: The median particle size D50 and specific surface area of the sulfide electrolyte are 10nm to 5000nm and 1m 2 / g~15m 2 / g, and the particle size distribution of the sulfide electrolyte satisfies: 0.9≤(D90-D10) / D50≤2.
2. The sulfide electrolyte according to claim 1, characterized in that Satisfy at least one of the following conditions: (1) The sulfide electrolyte satisfies the chemical formula Li 7-x P 1-y M y S 6-x-z N z W x , wherein 0≤x≤2, 0≤y<1, 0≤z<1, M includes at least one of As, Ge, Si, Sn, Sb, Nb, Al, N includes at least one of O and Se, and W includes at least one of halogen atoms; (2) The ionic conductivity of the sulfide electrolyte is 1 mS / cm to 15 mS / cm.
3. The sulfide electrolyte according to claim 1 or 2, characterized in that Satisfy at least one of the following conditions: (1) The D50 of the sulfide electrolyte is 20 nm to 500 nm, and can be optionally 250 nm to 300 nm; (2) The specific surface area of the sulfide electrolyte is 6 m 2 / g~13m 2 / g, optional 6m 2 / g~8m 2 / g; (3) The D90 of the sulfide electrolyte is 400nm to 450nm; (4) The D10 of the sulfide electrolyte is 100 nm to 150 nm; (5) The sphericity of the particles of the sulfide electrolyte is 0.5 to 1.
4. A method for preparing a sulfide electrolyte, characterized in that: include: The sulfide electrolyte raw material is subjected to a first liquid-phase ball milling to prepare a precursor slurry, wherein the sulfide electrolyte raw material is a mixture comprising a lithium source, a phosphorus source, a sulfur source and a halogen source; The precursor slurry is subjected to a first sintering treatment and a second sintering treatment in sequence to prepare a sulfide electrolyte intermediate product, wherein the temperature of the first sintering treatment is less than the temperature of the second sintering treatment; The sulfide electrolyte intermediate product is subjected to a second liquid-phase ball milling and then the ball milling solvent is removed to prepare a sulfide electrolyte, wherein the median particle size D50 and the specific surface area of the sulfide electrolyte are 10 nm to 5000 nm and 1 m 2 / g~13m 2 / g, and the particle size distribution of the sulfide electrolyte satisfies: 0.9≤(D90-D10) / D50≤2.
5. The preparation method according to claim 4, characterized in that: Satisfy at least one of the following conditions: (1) The temperature of the first sintering treatment is 120° C. to 300° C.; (2) The temperature of the second sintering treatment is 350°C to 700°C.
6. The preparation method according to claim 4 or 5, characterized in that: Satisfy at least one of the following conditions: (1) The average particle size of the sulfide electrolyte raw material is 0.5 μm to 10 μm, and can be optionally 0.5 μm to 8 μm; (2) In the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source and the halogen source is ≤2 μm; (3) The lithium source includes at least one of lithium sulfide, lithium oxide and lithium carbonate, and lithium sulfide may be selected; (4) The phosphorus source includes at least one of phosphorus pentasulfide and phosphorus trisulfide; (5) The sulfur source includes at least one of lithium sulfide, phosphorus pentasulfide and phosphorus trisulfide; (6) The halogen source comprises at least one of lithium chloride and lithium bromide; (7) The sulfide electrolyte raw material further comprises at least one of a simple substance of an M element, a compound containing an M element, and a compound containing an N element, wherein the M element comprises at least one of As, Ge, Si, Sn, Sb, Nb, and Al, and the N element comprises at least one of O and Se; Optionally, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source, the halogen source and the compound containing the element M is ≤2 μm; Optionally, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source, the halogen source and the N-containing element compound is ≤2 μm; Optionally, in the sulfide electrolyte raw material, the absolute value of the difference in average particle size between any two of the lithium source, the phosphorus source, the sulfur source, the halogen source, the M-containing compound and the N-containing compound is ≤2 μm.
7. The preparation method according to claim 4 or 5, characterized in that: Satisfy at least one of the following conditions: (1) After the first liquid phase ball milling, the particle size of the prepared precursor slurry is 1 μm to 7 μm; (2) the ball milling solvents used in the first liquid-phase ball milling and the second liquid-phase ball milling each independently include at least one of an ether organic solvent, an ester organic solvent and a nitrile organic solvent; Optionally, the first liquid-phase ball milling and the second liquid-phase ball milling use the same ball milling solvent; Optionally, the ether organic solvent includes at least one of dimethyl ether, dipropyl ether, dibutyl ether, methyl ethyl ether and anisole; Optionally, the ester organic solvent includes at least one of ethyl acetate, butyl butyrate, hexyl butyrate and isobutyl isobutyrate; Optionally, the nitrile organic solvent includes at least one of acetonitrile, isobutyronitrile, tert-butyronitrile and benzonitrile.
8. The preparation method according to claim 4 or 5, characterized in that: Satisfy at least one of the following conditions: (1) The ball-to-material ratio of the first liquid-phase ball milling is 5:1 to 40:1, and the liquid-to-material ratio is 1:1 to 10:1; (2) The ball-to-material ratio of the second liquid phase ball milling is 4:1 to 20:1, and the liquid-to-material ratio is 1:1 to 5:
1.
9. A solid-state battery, characterized in that: The invention comprises the sulfide electrolyte according to any one of claims 1 to 3 or the sulfide electrolyte prepared by the preparation method according to any one of claims 4 to 8.
10. An electronic device, characterized in that: Including the solid-state battery as described in claim 9.
Citation Information
Patent Citations
Carbon-containing sulfide solid electrolyte, preparation method and all-solid-state lithium secondary battery
CN116960443A
Sulfide and preparation method thereof, solid electrolyte, all-solid-state battery and electric equipment
CN117594868A
Cited By
Sulfide electrolyte, preparation method thereof and solid-state battery
CN121812764A
Solid-state electrolyte, solid-state electrolyte membrane and preparation method thereof, and solid-state battery
CN121905944A
High-dispersity sulfide solid electrolyte composite material, preparation method thereof and all-solid-state battery
CN122118049A
Sulfide solid-state electrolyte and preparation method therefor, battery cell, battery device, and electric device
WO2026077064A1